Insertion Sequences as Highly Resolutive Genomic Markers for Sequence Type 1 Legionella pneumophila Paris - Vergnes, Mike (American Society for Microbiology (ASM), 2011)
The causative agent of legionellosis, Legionella pneumophila, colonizes all natural and human-made water networks, thus constituting the source of contaminated aerosols responsible for airborne human infections. Efficient control of infections, especially during epidemics, necessitates the fastest and most resolutive identification possible of the bacterial source for subsequent disinfection of reservoirs. We thus compared recognized typing approaches for Legionella with a method based on characterization of insertion sequence (IS) content. A total of 86 clinical or environmental isolates of L. pneumophila, including 84 Paris isolates, sampled from 25 clinical investigations in France between 2001 and 2007, were obtained from the Legionella National Reference Center. All strains were typed by monoclonal antibody subgrouping, sequence-based typing, pulsed-field gel electrophoresis, and restriction fragment length polymorphism based on the presence or absence of IS elements. We identified six different types of IS elements in L. pneumophila Paris and used them as genomic markers in hybridization experiments. One IS type, ISLpn11, revealed a high discriminatory power. Simpson's index of discrimination, calculated from the distribution of IS elements, was higher than that obtained with the other typing methods used for L. pneumophila Paris. Moreover, specific ISLpn11 copies were found only in strains isolated from particular cities. In more than half of the cases, each clinical isolate had an ISLpn11 profile that was recovered in at least one environmental isolate from the same geographical location, suggesting that our method could identify the infection source. Phylogenetic analysis suggests a clonal expansion for the L. pneumophila Paris strain.